Foreign Language Input Initial Processing - Rast, Rebekah (Second Language Acquisition, 2008)
Foreign Language Input: Initial Processing presents the most comprehensive study to date of the starting point of second language acquisition. Its focus is on the language input that learners receive and what they actually do with this input. The empirical study detailed in the book follows a methodology in which all of the language input provided to the learners from the moment of first exposure is controlled, recorded and transcribed. This input is then quantitatively compared to the learners’ performance on language tasks administered at various time intervals up to 8 hours after first exposure. This in-depth analysis of the input and the learners’ performance sheds light on questions still unanswered in second language acquisition literature, such as what knowledge is brought to the acquisition process and how learners use this knowledge to process new linguistic information